2014
DOI: 10.1016/j.ijfoodmicro.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of σB and PrfA to Listeria monocytogenes salt stress under food relevant conditions

Abstract: Listeria monocytogenes is well known to survive and grow under several stress conditions, including salt stress, which is important for growth in certain foods as well as for host infection. To characterize the contributions, to salt stress response, of transcriptional regulators important for stress response and virulence (i.e., σ(B) and PrfA), we analyzed three L. monocytogenes parent strains and isogenic mutants (ΔsigB, ΔprfA, and ΔsigBΔprfA), representing different serotypes and lineages, for their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
1
28
1
Order By: Relevance
“…While previous studies have shown that a prfA null deletion had no effect on L. monocytogenes survival of 11% salt stress (Ribeiro et al, 2014), an increase in osmolarity may serve as a signal for the imminent encounter of the pathogen with host cells in the duodenum, where the osmolarity is higher than in previously encountered gastrointestinal compartments due to the breakdown of gastric contents into smaller molecules. Therefore, increased osmolarity may represent an environmental signal that is used by L. monocytogenes to sense its presence in a host environment where induction of PrfA activity is needed to facilitate invasion of host cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While previous studies have shown that a prfA null deletion had no effect on L. monocytogenes survival of 11% salt stress (Ribeiro et al, 2014), an increase in osmolarity may serve as a signal for the imminent encounter of the pathogen with host cells in the duodenum, where the osmolarity is higher than in previously encountered gastrointestinal compartments due to the breakdown of gastric contents into smaller molecules. Therefore, increased osmolarity may represent an environmental signal that is used by L. monocytogenes to sense its presence in a host environment where induction of PrfA activity is needed to facilitate invasion of host cells.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, we hypothesized that σ B and PrfA activities differ in individual bacteria in response to several environmental conditions. We chose two conditions shown previously to induce σ B activity: heat or salt stress (i.e., exposure to 45°C or 4.4% NaCl) (Sue et al, 2003; Hu et al, 2007; Abram et al, 2008; Somolinos et al, 2010; Ait-Ouazzou et al, 2012; Ringus et al, 2012; Ribeiro et al, 2014). Water phase salt concentrations in the range of 4% are typical in food preservation, and salt is used in the preservation of foods linked to human listeriosis cases and outbreaks (e.g., cheese or deli meat; Gottlieb et al, 2006; Currie et al, 2015; Heiman et al, 2016; McIntyre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…LI strains have been shown to be more salt tolerant than LII strains (Bergholz et al, 2010) and serotype 4b strains to be more salt tolerant than serotype 1/2a and 1/2b strains (Van Der Veen et al, 2008; Bergholz et al, 2010; Ribeiro et al, 2014). In the present study, no significant differences were found between the growth rates of different serotypes in 6% NaCl, however, five times as many 4b isolates were classified as salt tolerant as were classified as salt sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies which evaluated the stress tolerances of L. monocytogenes isolates have focused on associating phenotypes with genetic lineages (Bergholz et al, 2010), serotypes (Junttila et al, 1988; Barbosa et al, 1994; Ribeiro et al, 2014), and isolation sources (Begot et al, 1997; Durack et al, 2013). However, few significant differences between these groups were observed, suggesting that the diversity among isolates within these means of classification is not definitive for predicting phenotypic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have analyzed the transcriptomes of foodborne pathogens under stress conditions commonly present on/in food matrices (including hyperosmotic stress, cold stress, hydrostatic pressure stress, antimicrobial stress, acid stress, and alkali stress), using laboratory media modified to simulate these conditions as a model (15)(16)(17)(18)(19)(20)(21)(22)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). These laboratory media include BHI broth (18,20,21,59), BHI agar (19), Luria-Bertani broth (60,61), tryptic soy broth (62), M9-glucose (63), and Listeria minimal medium (22) as reference conditions.…”
Section: Discussionmentioning
confidence: 99%